Effect of growth regulators on shoot induction and plant regeneration in tomato (Lycopersicon esculentum Mill.) - Das, Amitav (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirement for the degree of Masters of Science in Biotechnology, 2011